Основи технології формування композиційних гідрогелевих плівок з кополімерів полівінілпіролідону та полікапроаміду - Яцульчак, Галина Володимирівна (Національний університет "Львівська політехніка", 2021)
У дисертаційній роботі розроблено основи технології формування композиційних гідрогелевих мембран на основі рідкоструктурованих кополімерів полівінілпіролідону з п-2-ГЕМА та полікапроаміду і визначені характерні для мембран властивості. Встановлено, що використання полівінілпіролідону з молекулярною масою 12·103г/моль у зміцнювальному шарі з ПА-6/ПВП та полівінілпіролідону з молекулярною масою рівною 360·103 г/моль у мембраніпідкладці забезпечує ефективну дифузію розчину у поверхневий шар гідрогелевої плівки, що сприяє утворенню щільної поверхневої плівки та формуванню композиційної гідрогелевої мембрани підвищеної міцності, з можливістю направленого регулювання її дифузійної проникності. Утворення зміцнювального приповерхневого шару на основі ПА-6/ПВП композиційних мембран підтверджується за допомогою сканувальної електронної мікроскопії та рентґено–структурного аналізу. Досліджено вплив складу формувальної суміші, умови формування і обробки композиційної мембрани на фізико-механічні, сорбційні властивості та селективно–транспортні характеристики плівок мембранного типу. Встановлено, що гідрогелеві плівки, модифікувані тонким шаром суміші ПА-6/ПВП з розчину у мурашиній кислоті, підвищеної міцності, можуть бути використані в медицині та фармацевтиці. Підтверджена придатність сформованих мембран в процесах осмосу, а також під час освітлення препаратів “Гентаміцину сульфат” та “Корглікон”, для очищення води від солей важких металів тощо. В диссертационной работе разработаны основы технологии формирования композиционных гидрогелевых пленок на основе жидкоструктуированих сополимеров поливинилпирролидона и поликапроамида и определены характерные для мембран свойства. Установлено, что использование поливинилпирролидона с молекулярной массой 12·103 г/моль в укрепляющем слое из ПА-6 и поливинилпирролидона с молекулярной массой ровной 360·103 г/моль в мембране-подкладке обеспечивает эффективную диффузию раствора в поверхностный слой гидрогелевой пленки, что способствует образованию плотной поверхностной пленки и формированию композиционной гидрогелевой мембраны повышенной прочности, с возможностью направленного регулирования ее диффузионной проницаемости. Образование укрепляющего приповерхностного слоя на основе ПА-6/ПВП композиционных мембран подтверждается с помощью сканирующей электронной микроскопии и ренгено - структурного анализа. Изучено влияние состава формующей смеси, условия формирования и обработки на физико-механические, сорбционные свойства и селективнотранспортные характеристики пленок мембранного типа. Установлено, что гидрогелевые пленки модифицированы тонким слоем смеси ПА- 6/ПВП из раствора в муравьиной кислоте и формирование композиционной гидрогелевой мембраны повышенной прочности, могут быть использованы в медицине и фармацевтике. Подтвержденная пригодность сформированных мембран в процессах осмоса, а также во время осветления препаратов "Гентамицина сульфата" и "Коргликона", для очистки воды от солей тяжелых металлов и т.п. The dissertation deals with the development of technological basics of composite hydrogel films formation via physical modification by a polycaproamide with polyvinylpyrrolidone (PA-6/PVP) mixture, which is a liquid-crosslinked copolymer of (polyvinylpyrrolidone) PVP and 2-hydroxyethyl methacrylate (2-НEMA), and with determination of physico-mechanical and physico-chemical properties typical of membranes. It was found that polyvinylpyrrolidone with a molecular weight of 12·103 g/mol in the strengthening layer of PA-6/PVP and with a molecular weight of 360·103 g/mol in the substrate membrane promotes the formation of a composite hydrogel membrane of high strength. Researches have shown that PA-6/PVP based films are effective for modifying the highly permeable hydrogel membranes allowing to form functionally strengthened selectively permeable nanolayers on their surface. It is defined that by the selection of the composition and concentration of the modifying solution of PA-6/PVP in formic acid can be used to regulate the physico-mechanical and selective-diffusion properties of the obtained composite hydrogel membranes. The formation of a strengthening near-surface layer based on PA-6/PVP composite membranes was confirmed by scanning electron microscopy and X-ray structure analysis. Researches have shown that PA-6/PVP based films are effective for modifying the highly permeable hydrogel membranes allowing to form selectively permeable strengthened nanolayers on their surface. To regulate the physicomechanical and selective-diffusion properties of composite hydrogel membranes it is necessary to select the composition and concentration of the modified solution of PA-6/PVP. When analyzing the experimental results and the regularities of deformation-strength properties it is possible to give a conclusion that the synthesized composite hydrogel membranes can have better physical and mechanical properties which in most cases are higher, than those of the initial hydrogel films. The influence of the forming mixture composition, the formation and processing conditions on the physico-mechanical and sorption properties, as well as on selective-transport characteristics of membrane-type films has been investigated. The technological basics of the composite polycaproamide-hydrogel films formation have been developed, their operational properties were investigated and the directions of practical application were proposed. It was found that hydrogel films of high strength modified with a thin layer of the PA-6/PVP mixture from a formic acid solution can be used in medicine and pharmaceutics. The suitability of the formed membranes for the osmosis process, for the clarification of "Gentamicin sulfate" and "Korglikon" drugs, for the purification of water from heavy metal salts, etc. have been confirmed. A method for forming high-strength tubular products from composite hydrogels based on HEMA-PVP copolymers has been developed.
Основы технологии формирования композиционных гидрогелевых пленок из сополимеров поливинилпирролидона и поликапроамида
Technological basics of composite hydrogel films formation from polyvinylpyrrolidone copolymers and polycaproamide
Keywords: гідрогель; 2-гідроксіетилметакрилат; полівінілпіролідон; полікапроамід; композиційна мембрана; гидрогель; 2-гидроксиэтилметакрилат; поливинилпирролидон; поликапроамид; композиционная мембрана; hydrogel; 2-hydroxyethyl methacrylate; polyvinylpyrrolidone; polycaproamide; composite membrane; 678.743.2:544.773.432-025(043.5)67